Multi-jet electrospinning of polystyrene/polyamide 6 blend: thermal and mechanical properties - Yoon, Jae Won; Park, Yaewon; Kim, Jooyoun; Park, Chung Hee (My University, 2017)
Polystyrene (PS) has high thermal resistance thus can be applied as thermally comfortable textile. However, the application is limited due its low mechanical strength. In this study, polyamide 6 (PA6) was blended with PS to improve the mechanical strength of PS, by means of a multi-jet electrospinning. Content ratio of the blend web was measured by chemical immersion test and confocal microscopy analysis. Fiber content was in accordance with the number of syringes used for PS and PA6 respectively. The effects of content ratio on the web morphology, thermal resistance, tensile behavior, air and water vapor permeability, and surface hydrophilicity were investigated. The influence of environmental humidity during electrospinning process on three dimensional (3D) web structure was also reported. PS web produced from higher humidity had more pores and corrugations at the surface. The increased surface roughness and porosity led to the increased hydrophobicity and thermal resistance. Though the blending of PA6 with PS enhanced the mechanical strength, the added PA6 decreased air/water vapor permeability and thermal resistance. The lowered thermal resistance by the addition of PA6 was mainly attributed to higher thermal conductivity of PA6 material and lowered air content with PA6 fibers.
Citation: Yoon, J. W., Park, Y., Kim, J., & Park, C. H. (2017). Multi-jet electrospinning of polystyrene/polyamide 6 blend: thermal and mechanical properties. Fashion and Textiles, 4, 12. doi:10.1186/s40691-017-0090-4
Keywords: Multi-Jet Electrospinning; Polystyrene; Polyamide 6; Thermal Resistance; Porosity; Surface-Morphology